Slavery and Sexual Availability - Glancy, Jennifer A. (The Oxford handbook of New Testament, gender, and sexuality, 2019)
Any investigation of slavery in the Roman Empire must contend with the sexual exploitation of slaves endemic to the system. Given the diversity of ancient Christian attitudes toward sexuality, there is no reason to expect that a slaveholding ethos touched all Christian communities in a uniform fashion. At issue, however, is not whether the wider context of a slaveholding empire affected the formation of Christian attitudes toward sexuality. At issue is how. The purpose of this essay is to question whether early Christian silence on the issue should be construed as wholesale rejection of a system in which social status scripted social morality, or as complicity with that system. In the end, it is difficult to imagine how the churches could have challenged the right of a male slaveholder to exploit his domestic slaves sexually without challenging his right to claim ownership of other human beings.